The effect of different types of physical activity on cognitive reaction time in older adults in China - Liu, Yujie; Hou, Xiao; Tang, Zhengyan; Zhang, Hanyue; Liu, Jingmin (Frontiers in Public Health, 2022)
Introduction: Aging is not only reflected in the degeneration of physiological functions but also embodied in the decline of psychological and cognitive functions. The decline of cognitive function can reduce the quality of life in older adults, and even potentially cause Alzheimer’s disease, which may lead to a heavy burden on patients, families, and society. The purpose of this study was to investigate the effects of physical activity (PA) on cognitive reaction time in older adults. Methods: A cross-sectional survey design was used in this study. A total of 839 elderly subjects were recruited from Beijing and Shanghai. And 792 subjects met the inclusion criteria (age > 60 years, without disability, speech and hearing impairment), including 384 males (age:67.7±5.7 years) and 408 females (age:68.2±5.8 years). The PA was assessed by the Physical Activity Scale for the Elderly (PASE). All kinds of PA were divided into three levels: “Low” (< 50% average score), “Moderate” (50% ~150% average score), and “High” (>150% average score). The reaction time of subjects was measured by the selective reaction tester (Model: CSTF-XF, TFHT, Beijing, China). Results: For leisure time PA, the results showed that the cognitive reaction time of old adults in the “Low” group (1.11±0.32s) was significantly longer than that in the “Moderate” (1.05±0.30s, p＜0.01) and “High” group (0.99±0.28s, p＜0.01). For housework PA, there was no significant difference in the cognitive reaction time among the three groups (“Low”: 1.09±0.31s; “Moderate”: 1.07±0.31s; “High”: 1.05±0.28s, p＞0.05). For work-related PA, the results showed that the cognitive reaction time of old adults in the “Low” group (1.09±0.30s) was significantly longer than that in the “High” (0.99±0.28s) and “Moderate” group (1.03±0.32s, p＜0.01). Conclusions: The PA has a positive effect on reducing cognitive reaction time in older adults. It is recommended that older adults maintain a moderate level of leisure PA and work-related PA to delay the decline in cognitive reaction time.